THE ROLE OF ANTIOXIDANTS IN REDUCING OXIDATIVE STRESS AND PREVENTING CHRONIC DISEASES - O`ktamova N.B.,; Boymuratov F.T., (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: Oxidative stress, caused by an imbalance between reactive oxygen species (ROS) production and the body’s antioxidant defense system, is a key factor in the pathogenesis of numerous chronic diseases, including cardiovascular disorders, diabetes, neurodegenerative conditions, and cancer. Antioxidants, both enzymatic and non-enzymatic, play a critical role in neutralizing free radicals and maintaining cellular redox homeostasis. Pharmacological and natural antioxidant preparations, including vitamins, polyphenols, flavonoids, and trace elements, have demonstrated significant clinical benefits in reducing oxidative damage, inflammation, and tissue degeneration. This article reviews the mechanisms of oxidative stress, the clinical importance of antioxidant therapy, and the potential of antioxidant interventions in preventing and managing chronic diseases.